The Solanum lycopersicum auxin response factor SlARF2 participates in regulating lateral root formation and flower organ senescence. (March 2017) - Ren, Zhenxin; Liu, Ruiyuan; Gu, Wenting; Dong, Xicun
Highlights: The expression of SlARF2 exists in all plant tissues but exhibits higher accumulation in tomato flowers. SlARF2 transcript level is regulated by Auxin, ethylene and GA. SlARF2 stimulates lateral root growth in Micro-Tom . SlARF2 also regulates flower organ senescence. SlARF2 regulates the expression of auxin responsive genes. Abstract: ARF2 as apleiotropic developmental regulator has been reported in Arabidopsis thaliana and tomato ( Solanum lycopersicum ). The present study showed SlARF2 transcripts in all tomato plant tissues but with higher accumulation in flowers. During bud–anthesis stages, SlARF2 transcripts showed a dynamic expression pattern in sepal, stamen, ovary and petal. Hormone treatment analysis suggested that SlARF2 transcript accumulation was positively regulated by auxin and gibberellic acid, and negatively regulated by ethylene in tomato seedlings. Phenotypes and molecular analyses of SlARF2 -upregulated transgenic tomato indicated that SlARF2 regulated tomato lateral root formation and flower organ senescence may be partially mediated by regulating the gene expression of auxin and ethylene response factors. The data enlarges the functional characterization of SlARF2 in tomato, and broadens our understanding of auxin signaling in regulating plant growth and development.